2018
DOI: 10.1111/jdv.14925
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical identification of nail matrix melanocytes

Abstract: The use of IHC significantly increases and facilitates the identification of melanocytes in unilateral biopsies. Our IHC counts exceed the averages found in the literature. This finding warrants new studies to verify whether the Colombian population presents higher numbers of melanocytes in the nail matrix than other populations or whether the observed increase is a result of the use of MiTF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…13,31,[41][42][43][44] Within the proximal nail matrix, melanocytes may be found in the suprabasal layers and are difficult to distinguish from adjacent keratinocytes. 13,30,[44][45][46][47] These features make interpreting pagetoid spread and melanocyte crowding difficult.…”
Section: Evaluation Of Atypiamentioning
confidence: 99%
See 1 more Smart Citation
“…13,31,[41][42][43][44] Within the proximal nail matrix, melanocytes may be found in the suprabasal layers and are difficult to distinguish from adjacent keratinocytes. 13,30,[44][45][46][47] These features make interpreting pagetoid spread and melanocyte crowding difficult.…”
Section: Evaluation Of Atypiamentioning
confidence: 99%
“…Concerning architectural features of NUM include increased melanocyte count, confluence of melanocytes, florid pagetoid spread, predominance of single units, multinucleated melanocytes, or poor circumscription 13,31,41–44 . Within the proximal nail matrix, melanocytes may be found in the suprabasal layers and are difficult to distinguish from adjacent keratinocytes 13,30,44–47 . These features make interpreting pagetoid spread and melanocyte crowding difficult.…”
Section: Clinical Challengesmentioning
confidence: 99%
“…suggested that an increased number of scattered atypical melanocytes with large hyperchromatic nuclei in a partial nail matrix may provide a diagnostic clue to NMIS, when there is strong clinical suspicion. As the identification of melanocytes in the nail matrix is often difficult, immunohistochemistry staining with Melan‐A (MART‐1), HMB45, S‐100, SOX‐10, or MiTF is useful 24,57,58 . It should be noted that the sensitivity of the S‐100 protein immunostain is weak for intraepithelial melanocytes of the nail matrix, although it is more sensitive for dermal component than HMB‐45 and Melan‐A 59 …”
Section: Histopathology Findingsmentioning
confidence: 99%
“…As the identification of melanocytes in the nail matrix is often difficult, immunohistochemistry staining with Melan-A (MART-1), HMB45, S-100, SOX-10, or MiTF is useful. 24,57,58 It should be noted that the sensitivity of the S-100 protein immunostain is weak for intraepithelial melanocytes of the nail matrix, although it is more sensitive for dermal component than HMB-45 and Melan-A. 59 The presence of inflammatory cell infiltration favors early NM compared to benign melanonychia, as it indicates an oncogenic response to malignant melanocytes.…”
Section: Histopathology Findingsmentioning
confidence: 99%